The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.energyfuels.0c02808
|View full text |Cite
|
Sign up to set email alerts
|

New Technique for Enhancing Oil Recovery from Low-Permeability Reservoirs: The Synergy of Silica Nanoparticles and Biosurfactant

Abstract: Low-permeability reservoirs are characterized by small pore size and a complex strata structure that present challenges and opportunities in recovering petroleum. In this study, a new nanofluid composed of biosurfactant and silicon dioxide (SiO2) nanoparticles, hereby called bionanofluid, was proposed as potentially enhanced oil recovery agent to investigate the synergy of biosurfactant and nanoparticles on oil displacement from low-permeability reservoirs. Turbiscan Lab was used in stabilization analysis, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…The difference between the base liquids will directly affect the absorption effect of CO 2 , and the reported base fluids are listed as follows: (1) water, deionized (DI) water; 16 and (2) amine solutions, MEA, 17 methyldiethanolamine (MDEA), 18 diethanoleamine (DEA), 19 piperazine (PZ), 20 4-diethylamino-2-butanol (DEAB), 21 2-amino-2-methyl-1-propanol (AMP), 22 triethylenetetramine (TETA), 23 and MEA−MDEA. 24 In addition to the above-mentioned classification according to the type of base fluid, this review also classifies nanoparticles dispersed in a base fluid: (1) non-metallic oxide, SiO 2 25 and graphene oxide (GO); 26 (2) carbon-based adsorbent, carbon nanotubes (CNTs) 27 and multi-walled carbon nanotubes (MWCNTs); 28 (3) metal oxides, alumina (Al 2 O 3 ), 29 zinc oxide (ZnO), 30 magnesium oxide (MgO), 31 and copper oxide (CuO); 32 and (4) magnetic metal oxide, iron oxide (Fe 3 O 4 ) and ferric oxide (Fe 2 O 3 ). 33 Except for the above four types of common nanoparticles, a hybrid nanoparticle (NOHM) has been discovered in recent years.…”
Section: Classification and Preparation Of Nanofluidsmentioning
confidence: 99%
“…The difference between the base liquids will directly affect the absorption effect of CO 2 , and the reported base fluids are listed as follows: (1) water, deionized (DI) water; 16 and (2) amine solutions, MEA, 17 methyldiethanolamine (MDEA), 18 diethanoleamine (DEA), 19 piperazine (PZ), 20 4-diethylamino-2-butanol (DEAB), 21 2-amino-2-methyl-1-propanol (AMP), 22 triethylenetetramine (TETA), 23 and MEA−MDEA. 24 In addition to the above-mentioned classification according to the type of base fluid, this review also classifies nanoparticles dispersed in a base fluid: (1) non-metallic oxide, SiO 2 25 and graphene oxide (GO); 26 (2) carbon-based adsorbent, carbon nanotubes (CNTs) 27 and multi-walled carbon nanotubes (MWCNTs); 28 (3) metal oxides, alumina (Al 2 O 3 ), 29 zinc oxide (ZnO), 30 magnesium oxide (MgO), 31 and copper oxide (CuO); 32 and (4) magnetic metal oxide, iron oxide (Fe 3 O 4 ) and ferric oxide (Fe 2 O 3 ). 33 Except for the above four types of common nanoparticles, a hybrid nanoparticle (NOHM) has been discovered in recent years.…”
Section: Classification and Preparation Of Nanofluidsmentioning
confidence: 99%
“…Protection of the environment is currently a worldwide priority; thus, it is not surprising that the use of surfactants obtained from natural products is the focus of many recent studies [ 69 , 70 , 71 ]. Leaves and fruits of the Cedr or Zizyphus Spina-Christi (Middle East tree) contain many saponin compounds that are natural surfactants.…”
Section: Reviewmentioning
confidence: 99%
“…The main mechanisms involved in oil recovery improvement were wettability alteration to water-wet, IFT reduction, and mobility ratio improvement. Later, the use of rhamnolipid with silica was proposed by Wang et al [ 71 ] who also tested other natural surfactants such as sophorolipid and surfactin. Stable systems were achieved working with biosurfactant and nanoparticle concentrations below the critical micelle concentration and 1000 mg/L, respectively, in 3 %wt NaCl solutions.…”
Section: Reviewmentioning
confidence: 99%
“…In recent years, proven oil reserves in low-permeability reservoirs make up a growing percentage of the totally proven oil reserves worldwide. The main challenges associated with oil production in low-permeability reservoirs are as follows: (1) the oil production declines rapidly induced by the fast decrease in near-wellbore reservoir pressure during the primary recovery process using natural power; (2) the injection pressure increases with improved starting pressure gradient; (3) the efficiency of oil recovery with the water flooding process is poor due to low absorbing capacity . These phenomena are mostly caused by the existence of a starting pressure gradient in low-permeability reservoirs and the zones with high resistance and thick fluidity between oil and water wells .…”
Section: Introductionmentioning
confidence: 99%
“… 1 3 The main challenges associated with oil production in low-permeability reservoirs are as follows: (1) the oil production declines rapidly induced by the fast decrease in near-wellbore reservoir pressure during the primary recovery process using natural power; (2) the injection pressure increases with improved starting pressure gradient; (3) the efficiency of oil recovery with the water flooding process is poor due to low absorbing capacity. 4 These phenomena are mostly caused by the existence of a starting pressure gradient in low-permeability reservoirs and the zones with high resistance and thick fluidity between oil and water wells. 5 Previous studies have shown that enhancing oil recovery by gas injection (including natural gas injection, CO 2 injection, N 2 injection, air injection, flue gas injection, etc.)…”
Section: Introductionmentioning
confidence: 99%